FORMULASI SHORTENING MENGGUNAKAN FRAKSI-FRAKSI MINYAK SAWIT MELALUI PENDEKATAN SIFAT FISIKOKIMIAWINYA (Formulation of Shortening using Palm Oil Fractions via Physichochemical Properties Approach) - Hasibuan, Hasrul Abdi; Hardika, Aga Prima (Baristand Industri Banda Aceh, 2016)
This study was conducted to formulates hortening using palm oil and its fractions with nearly 4types of commercial products. Formula impersonation performed by determining the characteristics of thetarget product and raw materials of palm oil fractions. Furthermore, the raw material of palm oil and itsfractions were mixed with various ratios and then determined the characteristics to obtain products that wereequivalent to the target. Common parameters used to determine the characteristics of shortening product werefatty acids composition, iodine value, melting point and solid fat content. From formulation development onfour types of shortening were obtained formulase quivalent to the target product characteristics the shorteningby blending formulation techniques through imitation target product can be used to improve and develop theproduction of a variety of products shortening in the palm oil downstream industries.